Technology Enhanced Learning in higher education; motivations, engagement and academic achievement - Dunn, T.J.; Kennedy, M. (Computers and education, 2019)
Technology Enhanced Learning (TEL) has become a common feature of Higher Education. However, research has been hindered by a lack of differentiation between usage and engagement and not recognising the heterogeneity of TEL applications. The current study aimed to assess the impact of emotional, cognitive and behavioural engagement with TEL on students’ grades and to also look at how motivation levels differentially predict engagement across different types of TEL. In a sample of 524 undergraduate students, we measured engagement and usage of TEL, student learning motivations and self-report student grades. Our results indicate that intrinsic motivations predict engagement, whilst extrinsic motivations predict usage. Importantly, engagement was predictive of grades whereas usage was not. Furthermore, when TEL was broken down by type, the use of social media groups was a significant predictor of grade, whereas reviewing lecture slides/recordings, reading additional content and using course blogs/discussion boards were not. We conclude that a sole focus on usage of TEL is misleading. Implications for researchers and educators are discussed. •Engagement with, rather than usage of, TEL predicted academic achievement.•Intrinsically motivated students were more likely to engage with TEL.•In terms of specific technologies, student-created social media activity was most predictive of grades.